(untitled) (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2023)
This study reveals the da’wah of the Honda Club Indonesia (HCI) community in Mojokerto, which originally focused on motorcycle activities into a da’wah forum that provides benefits to the wider community. Through the application of social identity theory, the HCI Mojokerto community has succeeded in developing itself as a medium for da’wah and increasing the knowledge and understanding of members and the surrounding community. This research uses a qualitative approach with data collection methods through participant observation, in-depth interviews, and documentation of HCI Mojokerto community activities. The results showed that this community was able to utilize a common hobby, namely motorcycles, as a basis for providing da’wah value in every activity carried out. The HCI Mojokerto community actively carries out religious preaching-oriented activities, such as silaturahmi, social services, and religious pilgrimages. Through these activities, community members get to know each other, increase religious understanding, and strengthen social values. In addition, this community plays a role in empowering its members and the surrounding community through opportunities for self-development and contributions to social activities. The Honda Club Indonesia (HCI) community in Mojokerto being a forum for da’wah and community empowerment is a good example of the application of social identity theory. With a focus on da’wah and empowerment, the HCI Mojokerto community makes a positive contribution to strengthening religious and social values in the surrounding environment.